Paracrine Engineering of Human Cardiac Stem Cells With Insulin‐Like Growth Factor 1 Enhances Myocardial Repair. Issue 9 (September 2015) - Jackson, Robyn; Tilokee, Everad L.; Latham, Nicholas; Mount, Seth; Rafatian, Ghazaleh; Strydhorst, Jared; Ye, Bin; Boodhwani, Munir; Chan, Vincent; Ruel, Marc; Ruddy, Terrence D.; Suuronen, Erik J.; et al.
Abstract : Background: Insulin‐like growth factor 1 (IGF‐1) activates prosurvival pathways and improves postischemic cardiac function, but this key cytokine is not robustly expressed by cultured human cardiac stem cells. We explored the influence of an enhanced IGF‐1 paracrine signature on explant‐derived cardiac stem cell–mediated cardiac repair. Methods and Results: Receptor profiling demonstrated that IGF‐1 receptor expression was increased in the infarct border zones of experimentally infarcted mice by 1 week after myocardial infarction. Human explant‐derived cells underwent somatic gene transfer to overexpress human IGF‐1 or the green fluorescent protein reporter alone. After culture in hypoxic reduced‐serum media, overexpression of IGF‐1 enhanced proliferation and expression of prosurvival transcripts and prosurvival proteins and decreased expression of apoptotic markers in both explant‐derived cells and cocultured neonatal rat ventricular cardiomyocytes. Transplant of explant‐derived cells genetically engineered to overexpress IGF‐1 into immunodeficient mice 1 week after infarction boosted IGF‐1 content within infarcted tissue and long‐term engraftment of transplanted cells while reducing apoptosis and long‐term myocardial scarring. Conclusions: Paracrine engineering of explant‐derived cells to overexpress IGF‐1 provided a targeted means of improving cardiac stem cell–mediated repair by enhancing the long‐term survival of transplanted cells and surrounding myocardium.